Measurement report: Surface exchange fluxes of HONO during the growth process of paddy fields in the Huaihe River Basin, China - F. Meng; F. Meng; B. Han; B. Han; M. Qin; W. Fang; W. Fang; K. Tang; D. Shao; D. Shao; Z. Liao; Z. Liao; et al. (Atmospheric Chemistry and Physics)
Significant amounts of nitrous acid (HONO) released from soil affect the chemistry of the troposphere, thereby serving as a major precursor to hydroxyl radicals. However, the scarcity of in situ data on soil–atmosphere HONO exchange flux has constrained the understanding of emission mechanisms and the budget of reactive nitrogen. Herein, we performed measurements of HONO and NOx fluxes over paddy fields in the Huaihe River Basin. The entire experiment involved various agricultural-management activities, including rotary tillage, flood irrigation, fertilization, paddy cultivation and growth, and top dressing. HONO and NO exhibited more upward fluxes, whereas NO2 was deposited on the ground, with average hourly fluxes of 0.07±0.22, 0.19±0.53, and -0.42±0.44<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="64pt" height="10pt" class="svg-formula" dspmath="mathimg" md5hash="900c3ba40814daf98fdf82256a28df3d"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-24-14191-2024-ie00001.svg" width="64pt" height="10pt" src="acp-24-14191-2024-ie00001.png"/></svg:svg> nmol m−2 s−1, respectively. Continuous peaks in HONO and NO fluxes were observed during the rotary tillage period, and they exhibited a significant correlation (R=0.77). Moreover, a significant correlation (R=0.60) between HONO flux and the product of J(NO2) × NO2 was observed during the daytime. The results indicate that both biological emissions from soil and light-driven NO2 conversion are likely active, collectively influencing the diurnal pattern of HONO flux. A source analysis revealed that the unknown HONO source (Punknown) exhibited a diurnal pattern with higher daytime and lower nighttime values. Sensitivity tests demonstrated that photo-enhanced NO2 conversion on the ground could adequately explain Punknown, while nocturnal HONO production derived from soil emission fluxes (ranging from 0.32 to 0.79 ppbv h−1) could sufficiently elucidate nighttime Punknown values. Our study emphasized the variability in HONO fluxes across various agricultural-management activities, as well as the importance of heterogeneous NO2 conversion on ground surfaces and soil emissions in HONO production.